Comparative study of the possible gastroprotective effect of probiotic (lactobacillus plantarum) and ranitidine on indomethacin induced gastric ulcer in adult male albino rat - Walid Mostafa Said Ahmed, Ahmed EL Sayed Ahmed Amer, Ebrahim M. M. Fayed, Mohamed Dmerdash, Usama Bhgat El- Gazzar, Doaa Genedy, Moaaz M. Y. Awad (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Indomethacin is an anti-inflammatory drug which causes peptic ulcers as a result of its complication, For this reason, multiple experimental studies have been performed to search for new agents in order to treat or prevent gastric and duodenal ulcers. Probiotics are live microorganisms, and it has been stated by different studies that these bacteria have antioxidant and anti-inflammatory effects so; the aim of the present study is to compare the gastroprotective potential of probiotic lactobacillus plantarum, versus the anti-ulcer drug (ranitidine), against indomethacin-induced gastric ulcer in rats.